Ensuring compliance of SDLC documentation within large enterprises - Stonaiev, Matvii; Novák, Richard, 1973-; Luc, Ladislav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This bachelor thesis focuses on ensuring compliance with Software Development Life Cycle (SDLC) documentation in large enterprises and managing the risks associated with SDLC. The theoretical part of the project analyses in detail the key concepts associated with the SDLC and highlights the importance of documentation management in the software development process. It also discusses various SDLC methodologies and models that are in use in practice and can be implemented in large enterprises to ensure the quality and efficiency of software development. The literature research in the theoretical part will discuss the importance and benefits of documentation management within SDLC and provide an overview of relevant standards and norms in this area. It will also explore the obstacles and challenges that large enterprises may face when implementing an SDLC and the strategies that can be used to overcome them. The practical part will focus on the application of Risk Management methods to name the causes and consequences associated with the different level and quality of documentation produced during the SDLC. Appropriate qualitative research methods (interviewing, observation, experiment and document analysis...) will be used to develop the risk matrix. Emphasis will be placed on interviewing at least ten qualified professionals working in the field of software development and risk management. The interviews will be conducted to cover key aspects of the SDLC documentation and will focus, in particular, on issues related to risk identification and management. During the interviews, respondents will be asked to evaluate current practices in their companies and to identify areas for improvement. Based on the qualitative research with interviews and thematic analysis methods conducted, key conclusions will be drawn and key risks associated with ensuring compliance with SDLC documentation will be identified.
These findings will be used to develop a Mitigation Plan that will include specific actions and strategies to eliminate or reduce the identified risks. An appropriate framework (e.g. NIST, COBIT 5, ISO 31 000...) will be selected to address the risks associated with SDLC documentation and the recommendations in the recommended literature and appropriate methods for this area will be followed when conducting qualitative research. In the final part, the student will carry out an evaluation of the theoretical and practical part, including a discussion of his own conclusions.
Vedoucí práce: Richard Antonín Novák
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: aplikovaná informatika [obor bakal. práce]; bakalářské práce; bachelor's theses